Explicating the acceptance of virtual learning environment: The roles of channel expansion and the theory of self determination / Hew Teck Soon - Hew, Teck Soon (2017)
The Malaysian government has launched the 1BestariNet (1SmartNet) project to provide high-speed 4G mobile Internet access to 5.5 million students, 0.5 million teachers and 4.5 million parents from 10,000 schools spread over 329,847 squarekilometers along with the Frog VLE system. The goal of this study is to examine the determinants of VLE acceptance from the context of cloud-based Frog VLE from the perspective of school teachers by applying the Self Determination Theory (SDT), Channel Expansion Theory (CET) and the unique constructs of VLE contend design, interactivity, knowledge sharing attitude and trust-in-website. The research question is “What are the factors that may impact the intention to use the VLE for instructional effectiveness among teachers?”. The survey instrument was rigorously validated for face validity, content validity and reliability by expert panel members and practitioners using content validity index and Q-sort technique. A three-round English-Malay backtranslation was engaged to ensure translation equivalence. After getting the permissions from various stakeholders, 1,720 questionnaires were administered in first wave (T1) to collect the data of the respondents’ demographics and the independent variables. After a 4-months gestation period, dependent variables were gathered in second wave (T2). Based on the PLS analysis, SDT and CET constructs were found to be significant predictors for teachers’ intention to use the Frog VLE. Teachers’ specialization was found to have confounding effects on behavioral intention. Finally, behavioral intention was found to have significant influence on perceived instructional effectiveness. The research has contributed several theoretical and practical implications for scholars, MoE, FrogAsia, school administrators and other stakeholders.